New Pharmacological Opportunities for Betulinic Acid - Ríos, José Luis; Máñez, Salvador (Planta Medica, 2018)
Betulinic acid is a naturally occurring pentacyclic lupane-type triterpenoid usually isolated from birch trees, but present in many other botanical sources. It is found in different plant organs, both as a free aglycon and as glycosyl derivatives. A wide range of pharmacological activities has been described for this triterpenoid, including antiviral and antitumor effects. In addition, several other interesting properties have been identified in the fields of immunity and metabolism, namely antidiabetic, antihyperlipidemic, and anti-inflammatory activities. Taken together, these latter three properties make betulinic acid a highly interesting prospect for treating metabolic syndrome. The present review focuses on the therapeutic potential of this agent, along with several of its semisynthetic derivatives, which could open new frontiers in the use of natural product-based medicines.
Keywords: betulinic acid; metabolic syndrome; antiviral; antitumor; parasiticidal; anti-infectious